Opportunities for youth participatory action research to inform school district decisions. (1st May 2020) - Cohen, Alison K.; Ozer, Emily J.; Abraczinskas, Michelle; Voight, Adam; Kirshner, Ben; Devinney, Molly
Abstract : Background Youth participatory action research (YPAR) is an equity-focused approach intended to generate local knowledge and democratise the production of research evidence. Aims/objectives We explore the promise and challenges of YPAR to inform education policy decision making. We focus on California's Local Control Funding Formula (LCFF)'s Local Control and Accountability Plan (LCAP) initiative, which requires districts to engage with diverse stakeholders to make decisions. We provide a case example of California's Stockton Unified School District. Stockton currently uses the Peer Leaders Uniting Students's YPAR curriculum to inform their LCAP work. Key conclusions YPAR offers opportunities for new insights, and can be implemented successfully at scale. While Stockton was doing YPAR before LCFF and LCAP existed, they enabled Stockton to expand its YPAR programming, with the goal of using YPAR evidence to provide useful information for educational decision making, policies, and programmes. For example, one YPAR project focused on student tardiness and, using data from multiple sources, proposed lengthening the passing period so that it was physically possible to walk to class in the time permitted. Here, YPAR supports those people most affected by education policy ‐ the students ‐ to have the power to inform decisions that affect them. YPAR can broaden the set of evidence and perspectives that decision makers review to inform policy decisions. We encourage researchers and practitioners to study and create policy structures that support using YPAR to inform policy. We also encourage policy makers to develop more policies that can facilitate the use of YPAR, in education and beyond.